HD’S Criminal Liability of Drugs Traffickin Based On Article 114 Section (1) Jo. Article 132 Section (1) Law Number 35 of 2009 On Narcotics - A.A. Aditya Dharmasaputra (Faculty of Law, Merdeka University Surabaya, Indonesia, 2019)
The purpose of this research is to fulfill one of the requirements to earn a Bachelor of Law in Faculty of Law, University of Surabaya.The practical purpose of this paper is to determine whether HD, who buys and sells of narcotics can be held guilty as criminally responsible based on Article 114 paragraph (1) jo. Article 132 paragraph (1) Law Number 35 of 2009 on Narcotics. HD was asked by IJ to buy heroin. HD approved the request by IJ and IJ gave money IDR. 120.000,-. HD bought the heroin from D IDR. 100.000, -, thus he gained profit of 20.000, -, kept in his pockets. The police arrested him before he submitted the heroin to IJ. The judges of South Jakarta District Court adjudicated HD as proven of violating Article 112 paragraph (1) of the Law on Narcotics. The results of the study showed that HD can be held guilty as criminally responsible based on Article 114 paragraph (1) jo. Article 132 paragraph (1) of the Law on Narcotics because it has met the four elements of crime and proper clause on attempted in terms of being an intermediary of drugs transactions.